Perfluorinated substances and telomeres in an Arctic seabird: Cross-sectional and longitudinal approaches - Blévin, Pierre; Angelier, Frédéric; Tartu, Sabrina; Bustamante, Paco; Herzke, Dorte; Moe, Børge; Bech, Claus; Wing Gabrielsen, Geir; Ove Bustnes, Jan; Chastel, Olivier (Environmental Pollution, 2017)
International audience Telomeres are non-coding DNA repeats located at the termini of eukaryotic chromosomes, regulated by dynamic processes balancing shortening and maintenance. Despite a mechanism to slow-down telomere shortening, cell division leads to progressive attrition of chromosomes, leading to the onset of cellular senescence or apoptosis. However, telomere restoration based on telomerase activity is the primary mechanism for telomere maintenance. Telomere length is associated to health and survival and can be impacted by a broad panel of environmental factors. However, the effect of contaminants on telomeres is poorly known for living organisms. The aim of this study was to investigate relationships between some poly- and perfluoroalkyl substances (PFASs), body condition and telomere length by using both a cross-sectional and longitudinal approach in adult breeding Black-legged kittiwakes (Rissa tridactyla) from Svalbard. First, we examined the associations between absolute telomere length and PFASs contamination in a given year (cross-sectional approach). Second, we investigated the relationships between telomere dynamics and PFASs contamination within a two years’ time frame (longitudinal approach). Our results did not show any significant relationships of PFASs and body condition with absolute telomere length in a given year. Surprisingly, we found a positive and significant relationship between PFASs and telomere dynamics in both sexes with elongated telomere in birds bearing the highest concentrations of PFASs. Our study underlines (i) the need to investigate PFAS effects on telomere dynamics with a longitudinal approach and (ii) a potential positive effect of these contaminants on telomere length, with the most contaminated birds showing the slowest rate of telomere shortening or even displaying elongated ones. Our study is the first to report a relationship between PFASs and telomere length in free-living vertebrates. A possible underlying mechanism and other potential confounding factors are ...